1992
DOI: 10.1128/mcb.12.7.3041
|View full text |Cite
|
Sign up to set email alerts
|

Stable and specific association between the yeast recombination and DNA repair proteins RAD1 and RAD10 in vitro.

Abstract: The RAD1 and RADIO genes of Saccharomyces cerevisiae are two of at least seven genes which are known to be required for damage-specific recognition and/or damage-specific incision of DNA during nucleotide excision repair. RADi and RADIO are also involved in a specialized mitotic recombination pathway. We have previously reported the purification of the RADIO protein to homogeneity (L. Bardwell, H. Burtscher, W. A. Weiss, C. M. Nicolet, and E. C. Friedberg, Biochemistry 29:3119-3126, 1990). In the present studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 51 publications
2
63
0
Order By: Relevance
“…Thus these results rule out the theoretical possibility raised by these and other remarkable observations with respect to the ERCC3 gene in the yeast and Drosophila systems, namely that the ERCC3 -NER connection could be indirect, i.e. ERCC3 might control the expression of one or more (real) NER genes without being involved itself in this process (Gulyas and Donahue, 1992;Mounkes et al, 1992;Schaeffer et al, 1993 (Schiestl and Prakash, 1990;Bailly et al, 1992;Bardwell et al, 1992;Biggerstaff et al, 1993;van Vuuren et al, 1993). Using the in vitro NER assay Wood and coworkers have shown that the replication factors PCNA and HSSB (RPA) also participate in the post-incision stages of the NER reaction (Coverley et al, 1992;Shivji et al, 1992) Serizawa et al, 1993a,b) and a helicase activity (Schaeffer et al, 1993 (Gerard et al, 1991).…”
Section: Discussionmentioning
confidence: 40%
“…Thus these results rule out the theoretical possibility raised by these and other remarkable observations with respect to the ERCC3 gene in the yeast and Drosophila systems, namely that the ERCC3 -NER connection could be indirect, i.e. ERCC3 might control the expression of one or more (real) NER genes without being involved itself in this process (Gulyas and Donahue, 1992;Mounkes et al, 1992;Schaeffer et al, 1993 (Schiestl and Prakash, 1990;Bailly et al, 1992;Bardwell et al, 1992;Biggerstaff et al, 1993;van Vuuren et al, 1993). Using the in vitro NER assay Wood and coworkers have shown that the replication factors PCNA and HSSB (RPA) also participate in the post-incision stages of the NER reaction (Coverley et al, 1992;Shivji et al, 1992) Serizawa et al, 1993a,b) and a helicase activity (Schaeffer et al, 1993 (Gerard et al, 1991).…”
Section: Discussionmentioning
confidence: 40%
“…[ 35 S]-labeled FLAG-DISC1 protein was synthesized using the T7 transcription/translation-coupled reticulocyte lysate system (Promega, Hampshire, UK). The translation product was partially purified by ammonium sulfate precipitation as described previously (Bardwell et al, 1992) before use in peptide array analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Labeled proteins were partially purified by ammonium sulfate precipitation (28) and then resuspended in 50 l of Buffer A (50 mM Tris-HCl, pH 7.5, 100 mM NaCl, 10 mM MgCl 2 , 10% glycerol, 1 mM phenylmethylsulfonyl fluoride, 1 mM benzamidine HCl, 1 g/ml leupeptin, 2 g/ml aprotinin, and 1 g/ml pepstatin).…”
Section: Methodsmentioning
confidence: 99%